The Influence of the Hanging Ball Training Model and the Drill Smash Training Model on the Smash Skills of SMAN 1 Jeneponto Extracurricular Participants - Yasriuddin Yasriuddin; M. Said Zainuddin; Husriani Husain; Wahyudin Wahyudin (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. Based on observations, it was found that extracurricular participants at SMAN 1 Jeneponto required further mastery of the basic techniques of Smash volleyball. To address this, an experimental study was conducted to determine the effect of two types of training - the hanging ball training model and the drill smash training model - on the smash skills of these participants. The research method utilized in this study was a group design. Materials and methods. The study focused on participants of the volleyball extracurricular activity at SMAN 1 Jeneponto. The sampling technique used was proportional sampling with a sample size of 16 participants, and the groups were divided using ordinal pairing. The analysis techniques employed included descriptive test analysis, data normality tests, homogeneity tests, and hypothesis tests. The analysis was conducted using SPPS Version 26.00 at a 95% significance level. Results. The data analysis shows that both the hanging ball training model and the drill smash training model have a significant impact on the smash skills of extracurricular participants at SMAN 1 Jeneponto. The t-values obtained for both models were much higher than the t-table value of 2.365, indicating a strong impact. Additionally, there is a significant difference in the impact of the two training models on the smash skills of the participants. Conclusion. Based on statistical analysis, it has been determined that the drill smash training model is more effective than hanging ball training. The analysis revealed that the observed t value of 7,000 is significantly greater than the t table of 2.145, with a significance level of 0.001, which is well below the alpha level of 0.05. In other words, the evidence strongly suggests that the drill smash training model is the more effective of the two training methods.